AUDIT COMMITTEE ATTRIBUTES AND ENVIRONMENTAL DISCLOSURE PRACTICES: EVIDENCE FROM LISTED NIGERIA INDUSTRIAL GOODS FIRMS - Lukmon Adewale ADEOYE; Oluwatobi Samuel ELEBIMOYO; Fadekemi Ruth OLU-AKINOLA; Lateef Obasanjo ONIBONOKUTA; Abiodun OLAOLU (Malete Journal of Accounting and Finance)
In Nigeria’s industrial goods sector, environmental disclosures are essential for promoting corporate transparency and addressing stakeholders concern about sustainability. Audit committees as part of corporate governance structures are expected to influence the quality and constituency of these disclosures. This study examined the effect of audit committee attributes on environmental disclosure practices of Nigerian listed industrial goods firms. The population of the study cis the 13 industrial goods firms listed on the Nigeria Exchange Group (NGX) out of which 11 were purposively selected as the sample size based on availability of data. The study periods covered year 2011 to 2022. Descriptive statistics, correlation and panel regression analysis were utilized to analyze the data gathered for this study. Findings from this study revealed that audit committee meeting and audit committee size does not have any statistically significant effect on environmental disclosures (EVD) whereas audit committee independence (ACI) was found to have a significant positive effect on EVD evidenced with coefficient of 17.608. This implies that only ACI was found to have a notable impact on EVD. The study concludes that audit committees’ attributes in terms of audit independence can improve the disclosure of environmental practices. Thus, this study recommends that firms should ensure that audit committees (AC) should comprise entirely of independent members who do not have any financial or personal ties to management. Firms should also provide AC with specialized training in environmental issues and reporting standards.